New species of pyrrhulina (Ostariophysi: Characiformes: Lebiasinidae) from the brazilian shield, with comments on a putative monophyletic group of species in the genus - Netto-Ferreira, André L.; Marinho, Manoela M. F. [UNESP] (Magnolia Press, 2013)
Pyrrhulina marilynae, new species, is described. The new species can be distinguished among congeners mainly by pre-senting a conspicuous, dark, zigzag shaped primary stripe, extending to distal end of median caudal-fin rays, reduction of the number of precaudal vertebrae, absence of postcleithrum 2, and nine principal rays on caudal-fin dorsal lobe. The pu-tative relationship of the new species with Pyrrhulina australis, P. vittata and P. zigzag, three small-sized species of the genus, is discussed. Copyright © 2013 Magnolia Press.
Keywords: Neotropical; Pyrrhulina rachoviana; Pyrrhulininae; Systematics; Teleostei